2013
DOI: 10.1371/journal.pone.0062762
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Lewis Lung Carcinoma Tumor Control by Irradiation Using Diffusion-Weighted and Dynamic Contrast-Enhanced MRI

Abstract: PurposeTo investigate the correlation between diffusion-weighted (DW) and dynamic contrast-enhanced (DCE) magnetic resonance imaging (MRI) derived parameters and radioresponsiveness of Lewis lung carcinoma (LLC) tumor.Materials and MethodsLLC tumor growth in C57BL/6 mouse limb was used for the experiment. The tumors were irradiated with 10 Gy×5, or 30 Gy×2 vs. sham irradiation. Fourteen tumors were subjected to DW-MRI and DCE-MRI pre-radiotherapy and weekly imaging after radiotherapy. The temporal changes in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…DCE-MRI has been widely used to inform pharmacodynamic modeling that evaluates vascular perfusion and permeability in patients with different cancers. 8,[17][18][19][20] Our study demonstrated significant decreases in the SUV max , K trans mean, K trans SD, k ep mean, k ep SD, and v p SD. K trans characterizes the diffusive transport of low-molecular weight gadolinium chelates across the capillary endothelium, and it is regarded as a biomarker to assess antiangiogenic and antivascular therapies; k ep indicates the rate constant (k e P 5 K trans / v e ); v p indicates the plasma volume, and v e indicates extracellular volume.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…DCE-MRI has been widely used to inform pharmacodynamic modeling that evaluates vascular perfusion and permeability in patients with different cancers. 8,[17][18][19][20] Our study demonstrated significant decreases in the SUV max , K trans mean, K trans SD, k ep mean, k ep SD, and v p SD. K trans characterizes the diffusive transport of low-molecular weight gadolinium chelates across the capillary endothelium, and it is regarded as a biomarker to assess antiangiogenic and antivascular therapies; k ep indicates the rate constant (k e P 5 K trans / v e ); v p indicates the plasma volume, and v e indicates extracellular volume.…”
Section: Discussionmentioning
confidence: 49%
“…DCE‐MRI has been widely used to inform pharmacodynamic modeling that evaluates vascular perfusion and permeability in patients with different cancers . Our study demonstrated significant decreases in the SUV max , K trans mean, K trans SD, k ep mean, k ep SD, and v p SD.…”
Section: Discussionmentioning
confidence: 62%
“…A study of Zheng et al demonstrated that a higher Kep was associated with lower, concurrent chemoradiotherapy and there was a significant difference between the groups. Furthermore, it revealed that Ve was significantly increased at dose of 10 Gy and 30 Gy in animal tests of lung cancer . Kim found that Ve was positively correlated with tumour regression rate in the cervical cancer.…”
Section: Discussionmentioning
confidence: 93%
“…The selection of the correct model for the right tumor is limited by what is named the "mixed tissue conundrum" [69], and remains mainly driven by both its bias-variance tradeoff and clinical relevance. In this way, DCE Tofts models have become standards in oncology [70,71], and have shown preclinical and clinical relevance in lung cancer speci cally [15,16,72]. The dual AIF, however, has never been validated for dynamic PET analyses, and therefore cannot be considered as a reference.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of gadolinium (Gd), the K trans , v e , K ep (the K trans to v e ratio) and v p microparameters re ect the perfusion, permeability and microvascular density properties of the tumor [13]. Previous oncological studies showed DCE microparameters to be signi cant predictors of response to treatment in several malignancies [14][15][16][17], including NSCLC [18].…”
Section: Introductionmentioning
confidence: 99%